THE PREVALENCE OF H5N1 INFLUENZA VIRUS ON POULTRY AT TRADITIONAL MARKET IN SEMARANG, INDONESIA - R. Susanti (The East Java Biological Society, 2015)
Traditional market is a potential source of the spread of avian influenza virus. This research is aimed to determine the prevalence of avian influenza virus (AIV) subtype H5N1 on poultry sold in traditional market in Semarang City. Fifty-five poultry samples sold in six traditional markets in Semarang City; i.e. Karangayu market, Mangkang market, Gunungpati market, Rejomulyo market, Gayamsari market and Karimata market taken from its cloaca swab. Further, cloacal swab samples grown in pathogen-free chicken embryos aged nine days. Then, it incubated for four days at 37 °C. Allantoic fluid then collected and tested to agglutinate red blood cells. RNA extracted from the samples showed haemagglutination activity. Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) applied to identify the subtype of AIV using the specific primer H5 and N1. The PCR product resulted from RT-PCR then visualized using electrophoresis. The results showed that four AIV subtype H5N1 isolates have successfully isolated from cloacal swab samples (7.27%) with the distribution of 2 isolates were from Mangkang Market (28.57%), 1 isolate was from Rejomulyo Market (7.69%) and 1 isolate was from Karimata Market. The prevalence of AIV subtype H5N1 was 28.57% in Mangkang market, 7.69% in Rejomulyo market and 9.09% in Karimata market. The prevalence values of each species were 7.89% in chicken and 9.09% in the wild duck. According to this result, poultry sold in traditional market in Semarang have a potential source of AIV subtype H5N1.